Revision of scientific manuscripts by non-native English-speaking scientists in response to journal editors' language critiques. Issue 2 (25th August 2015) - Englander, Karent
Abstract : Scientists' manuscripts must fulfill the expectations of journal reviewers and editors in order to be published, whether the author's first language is English or not. However, manuscripts submitted by nonnative-English-speaking scientists are sometimes criticized for their language usage and they require revision. In some cases, these authors do revise their manuscripts, resubmit them, and have them accepted for publication. To date, little had been known about the linguistic changes scientists make to their manuscripts, nor had there been a close descriptive study of the textual revisions that served to satisfy the demands of journal editors. This study uses the systemic functional linguistics approach of discourse analysis to examine the changes made in a small corpus of manuscripts from nonnative-English-speaking scientists that were initially criticized, in part for their language usage, but were later accepted. The results demonstrate that the changes that were made at the lexicogrammatical level were not mere syntactic corrections, but altered the position of the scientist and his text in relation to the scientific community.